Indigofera cylindrica Indigo: FPS-282/FP282, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of Indigofera cylindrica, commonly known as indigo. It describes the plant’s physical characteristics, including its pinnately compound leaves, pink flowers, and rounded vase-shaped canopy. The document details the plant’s growth habits, soil and light requirements, and its moderate drought tolerance. It also highlights the plant’s uses in landscaping, such as specimen planting, border planting, and container gardening. Additionally, it notes that indigo is not native to North America and is not known to be invasive. The document concludes with practical advice on planting and maintaining indigo for optimal growth and aesthetic appeal. Original publication date October 1999.